Interaksi Obat dalam Terapi Insulin pada Pasien Diabetes Melitus Tipe 1: Studi Retrospektif - Intan Kumara Tungga; Dian Ayu Juwita; Rahmi Yosmar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Type 1 Diabetes Mellitus (T1DM) is a chronic autoimmune disorder resulting in the destruction of pancreatic β-cells, leading to absolute insulin deficiency and hyperglycemia. Insulin remains the cornerstone of therapy; however, its use may be complicated by drug interactions that alter treatment effectiveness through pharmacodynamic or pharmacokinetic mechanisms. This study aimed to evaluate the prevalence and mechanisms of potential insulin drug interactions in patients with T1DM. A retrospective, cross-sectional study was conducted using a total sampling method. The study was conducted at Dr. M. Djamil General Hospital Padang. The study population consisted of all hospitalized patients diagnosed with type 1 diabetes mellitus (T1DM) during the period 2019–2022. Patient characteristics, patterns of insulin therapy, and the occurrence of drug interactions were analyzed. The majority of patients were female (70%), and most were in the 0–18-year age group (83%). Insulin therapy was prescribed in 86.6% of cases. Potential drug–drug interactions were identified in 33.3% of hospitalized patients with type 1 diabetes mellitus, predominantly pharmacodynamic in nature. The basal–bolus insulin regimen constituted the most frequently prescribed therapeutic option among the patients. The Spearman correlation analysis indicated a statistically insignificant association between the metric of polypharmacy and the incidence of drug interactions. Systematic monitoring remains essential, and larger prospective studies are needed to confirm these findings.